Penggunaan Metode Elbow untuk Pemilihan Jumlah Klaster dalam Identifikasi Bahan Material Shelter Modular - SARI, SELY NOVITA; Pratama, Bagus Gilang; Prastowo, Rizqi (Institut Teknologi Nasional Yogyakarta, 2024)
Modular shelters have become a popular solution for temporary infrastructure construction, especially in disaster-affected areas. One of the main challenges is selecting the appropriate materials, which can be addressed through cluster analysis to group materials based on similar characteristics. The Elbow Method is used to determine the optimal number of clusters in this analysis, with the